HUBUNGAN TIPE KEPRIBADIAN DENGAN KECERDASAN INTERPERSONAL GURU DI TK SEKECAMATAN TAMPAN PEKANBARU - Ramadhani, Raikhaniel; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the relationship of personality types with the teacher interpersonal intelligence in TK sekecamatan Tampan Pekanbaru. The method used in this study is a quantitative correlation method. The population in this study are all undergraduate teacher sekecamatan Handsome pekanbaru which amounted to 51 people. Determination of the number of samples using probability sampling techniques as many as 51 teachers. The data collection techniques used are questionnaire (questionnaire). Data were analyzed using analysis of correlation person chi square statistics using SPSS Ver.20. The study hypothesis was a significant correlation between personality type. the teacher interpersonal intelligence. It can be seen from the analysis of the data obtained (r) of which lies in the range from 0.40 to 0.599 with a category quite strong / moderate. This means that there is a strong enough relationship /'m antaraTipe Personality with Interpersonal Intelligence .In addition, the results of the hypothesis can also be compared to the value rhitung and rtabel known rhitung 0.540 while rtabel (5%) dk = n-2 = 42-2 = 40 so rtabel 0.213 , Because rhitung greater than rtabel or 0540> 0.213, it can be concluded that there is a positive hubungn between variable types of personality with intelligence Interpersoanal teachers. the strength of the relationship between personality type with Interpersonal intelligence is strong enough / medium rhitung value of 0.540. In addition to knowing a significant hypothesis test